Quantitative analysis method of oil occurrences in tight reservoir - Haibo Li; Xiangui Liu; Zhengming Yang; Hekun Guo; Qingqiao Zeng; Lixin Meng; Feixiang Qin (Energy Reports, 2020)
Combining NMR, high-speed centrifugal experiment, high pressure mercury injection and physical simulation experiment technologies, a new quantitative analysis method of oil occurrences in tight reservoir is put forward and applied to two tight oil blocks. Research shows that percentage of free oil is low (about 18%) in tight reservoir, while adsorbed oil is high (about 43%). There is a positive correlation between percentage of free oil and permeability; Free oil in reservoirs greater than 0.1mD are approximately 26% and 35% in block A and B respectively, while in reservoirs less than 0.1mD are only about 12% and 17%. Free oil content controlled by micron-throats is low (only about 4% and 5% in block A and B respectively). Free oil is mainly controlled by Nano-throats. The amount of adsorbed oil on surface of larger pore-throats is the same as amount in small pore-throat in block A reservoir, while adsorbed oil in block B mainly occurs in small pore-throats. Amount of adsorbed oil on surface of larger pore-throat in block A reservoir greater than 0.1mD is lower than reservoir less than 0.1mD, while occurrence law of adsorbed oil in small pore-throat is opposite.
Keywords: 330; Adsorbed oil; Free oil; High speed centrifugation; NMR; Quantitative analysis; Tight reservoir